2020
DOI: 10.1042/bsr20200065
|View full text |Cite
|
Sign up to set email alerts
|

Tripartite motif containing 35 contributes to the proliferation, migration, and invasion of lung cancer cellsin vitroandin vivo

Abstract: The tripartite motif (TRIM) family is a family of proteins with highly conserved domains. Previous researches have suggested that the members of TRIM family proteins played a crucial role in cancer development and progression. Our study explored the relationship between TRIM35 and non-small cell lung cancer (NSCLC). The study showed that the expression of TRIM35 was increased in NSCLC samples, and patients with high expression of TRIM35 had a poor clinical prognosis. Overexpression of TRIM35 in NSCLC cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
(40 reference statements)
1
8
0
Order By: Relevance
“…For example, TRIM35 has been suggested as a driver of lung cancer development with potential diagnostic and prognostic value. 8 Similar findings have also been made for TRIM23 in colorectal cancer, 9 and for other 13 members of the TRIM family involvement in cancer stem self-renewal has been suggested. 10 TRIM24 is of particular interest in cancer biology.…”
supporting
confidence: 63%
“…For example, TRIM35 has been suggested as a driver of lung cancer development with potential diagnostic and prognostic value. 8 Similar findings have also been made for TRIM23 in colorectal cancer, 9 and for other 13 members of the TRIM family involvement in cancer stem self-renewal has been suggested. 10 TRIM24 is of particular interest in cancer biology.…”
supporting
confidence: 63%
“…As a key protein of E3 ubiquitin ligase, TRIM35 is widely involved in the regulation of various physiological and pathological processes in tumors ( 38 ). In non-small cell lung cancer, the expression of TRIM35 was observed to be increased in tumor samples, and high expression of TRIM35 was closely related to poor clinical prognosis of patients ( 39 ). Inhibition of TRIM35 expression in non-small cell lung cancer cell lines promoted cell proliferation, migration and invasion ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…In non-small cell lung cancer, the expression of TRIM35 was observed to be increased in tumor samples, and high expression of TRIM35 was closely related to poor clinical prognosis of patients ( 39 ). Inhibition of TRIM35 expression in non-small cell lung cancer cell lines promoted cell proliferation, migration and invasion ( 39 ). Another study reported that E3 ubiquitin ligase TRIM35 is expressed at a low level in diffuse large B-cell lymphoma ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…TRIM35 is a tumor suppressor in HCC but suppresses HCC cell tumorigenicity by blocking PKM2 phosphorylation ( 48 ). TRIM35 plays a vital role in the tumoral growth of lung cancer and might be a potential diagnostic and prognostic target for patients with lung cancer ( 49 ). Thus, TRIM35 exerts both oncogenic and tumor suppressor roles in diverse types of tumors and its role in KIRC requires further exploration.…”
Section: Discussionmentioning
confidence: 99%